2010
DOI: 10.1269/jrr.09143
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Biological Effects of Ion Beams on Lethality, Molecular Nature of Mutation, Mutation Rate, and Spectrum of Mutation Phenotype for Mutation Breeding in Higher Plants

Abstract: Recently, heavy ions or ion beams have been used to generate new mutants or varieties, especially in higher plants. It has been found that ion beams show high relative biological effectiveness (RBE) of growth inhibition, lethality, and so on, but the characteristics of ion beams on mutation have not been clearly elucidated. To understand the effect of ion beams on mutation induction, mutation rates were investigated using visible known Arabidopsis mutant phenotypes, indicating that mutation frequencies induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
152
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 238 publications
(153 citation statements)
references
References 63 publications
(67 reference statements)
0
152
0
1
Order By: Relevance
“…They have been accepted as an efficient technology for the mutation breeding of plants and microbes. Heavy-ion irradiation induces a broad spectrum of mutation phenotypes even at low irradiation doses and for short irradiation times (Tanaka et al, 2010;Abe et al, 2012). Heavy-ion irradiation has also been accepted as a powerful mutagen for both forward and reverse genetics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They have been accepted as an efficient technology for the mutation breeding of plants and microbes. Heavy-ion irradiation induces a broad spectrum of mutation phenotypes even at low irradiation doses and for short irradiation times (Tanaka et al, 2010;Abe et al, 2012). Heavy-ion irradiation has also been accepted as a powerful mutagen for both forward and reverse genetics.…”
Section: Introductionmentioning
confidence: 99%
“…The LET of γ-rays is 0.2 keV·μm -1 , whereas the LET of heavy-ion beams can be altered by selecting the ion species or controlling its velocity. It is well known that high-LET radiation shows stronger biological effects than low-LET radiation (Yatagai, 2004;Tanaka et al, 2010). We have studied the effect of LETs by using the model plant Arabidopsis thaliana.…”
Section: Introductionmentioning
confidence: 99%
“…The rice mutant traits were low amylose content, tillering ability, dwarf plants, and resistance to the pathogen. Tanaka et al ( 2010 ) mentioned that ionizing radiation could generate many kind of phenotypes, because it induces DNA damage relatively randomly, and therefore, induces a series of mutation. National Nuclear Energy Agency (NNEA/BATAN) has 20 rice varieties released since 1982, and the varieties should be resistant to diseases.…”
Section: Introductionmentioning
confidence: 99%
“…This technique is very effective at causing mutations in embryos at a particular stage of fertilization, without damaging other plant tissues (Abe et al 2002). Moreover, heavy ion irradiation, which induces a broad spectrum and high frequency as well as high diversity of mutants, has shown a great potential for breeding cultivars (Shikazono et al 2001;Tanaka et al 2010). Existing studies have demonstrated that ion irradiation caused irreparable DNA double-strand breaks (DSB), whereas most damage caused by traditional radiation resources (like X-ray and γ-ray) was repaired (Wada et al 2002).…”
mentioning
confidence: 99%
“…Taken together, these results support the conclusion that the combined effects of increased branches, pod numbers, and numbers of seeds contributed to significant enhancement of crop yields of hyl-1, hyl-2, and hyl-3. Although no obviously drought-and disease-sensitive or resistant phenotype to abiotic stress was observed in three mutant lines, irradiation treatment induces a variety of mutations in plants which are very important for plant breeding (Younis et al 2008;Tanaka et al 2010).…”
mentioning
confidence: 99%